Transforming Green Accounting Strategies in Online Transportation: A Critical Analysis - Putra, Allen Pranata; Wasiaturrahma, Wasiaturrahma; Supeno, Eko (AFRE (Accounting and Financial Review), 2023)
This study aims to explore the tightening of green accounting strategies and suggest the right use in online transportation companies. This research was conducted in East Java involving 112 research informants with several related public officials. This study uses in-depth interviews and data reduction as data collection techniques related to green accounting strategies. The right calculation to implement an environmental accounting strategy triggers Elkington’s three pillars, namely: 1) Environmental accounting; 2) Social accounting; 3) Financial accounting. The findings of conventional transportation research that want to survive in transportation services must be able to innovate at least the fundamental business mechanisms that are run. The application of green accounting has the potential to increase company profitability, this is based on significant influences that indirectly increase profitability. This increase is due to the positive image built in the community so that it makes a good comparative advantage. DOI: https://doi.org/10.26905/afr.v6i3.10454